Optimizing Purchase Decisions through Product Quality and Price on Retail MSMES - zuhra, fathia; Siregar, Ajizah Syahfitri; Tanjung, Tia Nava Utari; Anggraini, Tuti (Universitas Islam Negeri Sumatera Utara, 2023)
The study aims to analyze the impact of product quality and price on consumer purchasing decisions at Toko Gopek Medan. A quantitative method using multiple linear regression was employed. The findings reveal that product quality significantly influences purchasing decisions, with a positive regression coefficient indicating that improvements in product quality can enhance consumer purchasing decisions. Conversely, price does not show a significant effect on purchasing decisions, as evidenced by a p-value greater than 0.05. The adjusted R-squared value of 0.868 indicates that approximately 86.8% of the variation in purchasing decisions can be explained by product quality and price. These results suggest that Toko Gopek Medan should focus its marketing efforts on enhancing product quality to attract more consumers and increase sales. This research provides strategic insights for the future development of Toko Gopek's business.